ANALISIS USAHA DAN PEMASARAN AYAM PEDAGING (BROILER) POLA KEMITRAAN DI DESA BATHIN BETUAH, KECAMATAN MANDAU KABUPATEN BENGKALIS - Kelvin Andrian Pratama; Septina Elida (DINAMIKA PERTANIAN, 2024)
The broiler business has prospects for development. This study examines the broiler farming business and its marketing practices in Bathin Betuah Village. The research involved farmers and traders as respondents. Both qualitative and quantitative data were analyzed. The findings reveal that: 1) Broiler farming is a profitable venture, as indicated by a Return on Cost Ratio (RCR) of 1.12. Feed costs account for the largest proportion of production costs, comprising 72.20% of the total. 2) Two marketing channels were identified: Channel I involves farmers, partner companies, retailers, and household consumers, while Channel II connects farmers, partner companies, and direct consumers. The second channel demonstrates higher efficiency.